2019
DOI: 10.1111/jsr.12825
|View full text |Cite
|
Sign up to set email alerts
|

The role of couple sleep concordance in sleep quality: Attachment as a moderator of associations

Abstract: Summary Despite most American adults sharing a bed with a romantic partner, sleep research has examined sleep primarily as an individual behaviour. A growing body of research indicates that couple bed sharing may have an impact on sleep quality, but the current study is the first to examine whether such associations may differ based on attachment security. A sample of 179 cohabiting heterosexual couples completed daily sleep diaries and surveys of their attachment security, avoidance and anxiety. Data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Those components are combined into the global sleep quality scale; higher scores represent poorer sleep quality. The alpha levels were calculated using component scores ( α = .68), per recommendations (44) and were close to the range of alphas (.70 –.83) in prior studies (27). The ICC is 0.74 for the global sleep score, 0.59 for sleep quality, 0.68 for sleep latency, 0.67 for sleep duration, 0.55 for habitual sleep efficiency, 0.60 for sleep disturbance, and 0.57 for daytime dysfunction.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Those components are combined into the global sleep quality scale; higher scores represent poorer sleep quality. The alpha levels were calculated using component scores ( α = .68), per recommendations (44) and were close to the range of alphas (.70 –.83) in prior studies (27). The ICC is 0.74 for the global sleep score, 0.59 for sleep quality, 0.68 for sleep latency, 0.67 for sleep duration, 0.55 for habitual sleep efficiency, 0.60 for sleep disturbance, and 0.57 for daytime dysfunction.…”
Section: Methodsmentioning
confidence: 90%
“…Although people with high attachment avoidance report hyperindependence, they still benefit from feeling close and secure in their relationships. Higher levels of sleep concordance (when both members in a couple go to sleep and wake up at similar times) were associated with higher sleep quality for women with high attachment avoidance (27). Being physically close to one’s partner while going to bed, sleeping, and waking benefited those high in attachment avoidance (27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep is not an individual experience, but a social one, as many individuals have bed-sharing or co-sleeping partners (i.e., romantic partners; Andre et al, 2021). There is growing evidence that couples exhibit some concordance, or similarity, in sleep quality (Elsey et al, 2019;Hasler & Troxel, 2010;Walters et al, 2020a).…”
Section: Couples and Sleepmentioning
confidence: 99%
“…Sleep is not an individual experience, but a social one, as many individuals have bed‐sharing or co‐sleeping partners (i.e., romantic partners; Andre et al, 2021). There is growing evidence that couples exhibit some concordance, or similarity, in sleep quality (Elsey et al, 2019; Hasler & Troxel, 2010; Walters et al, 2020a). Early couples research found concordance in epoch‐by‐epoch, actigraphy‐assessed movement patterns, meaning that couples have similar sleep–wake patterns throughout the night (Pankhurst & Home, 1994).…”
Section: Introductionmentioning
confidence: 99%